Családok peremhelyzetben városon és falun (Szociológiai Szemle, 2024)
The paper analyses the experiences of case studies with 120 families that belong to those who were hit hardest by the economic and social transition. The steadily disadvantageous situation of these families can be traced back to the labor market processes. Despite decreasing unemployment figures and several labor market programs there are still large groups - young people, women with small children, elderly middle-aged persons, the Roma - who can hardly reintegrate into permanent employment. For these people no good choices exist between low wages of available and often uncertain, formal and official jobs and between the irregular incomes from casual, precarious work supplemented with social allowances and benefits. The mobilization of all family resources, including often the work of children, may help to overcome daily problems of subsistence, however their family system is often in danger. Market instability, the loss of continuous income, health problems, tensions and emotional crisis situations often jeopardize the daily conduct of life, housing conditions and the future of children. In the lack of other subsistence strategies and family models this instability is going to be reproduced by the younger generations.